Linking Workplace-Based Assessment to ACGME Milestones: A Comparison of Mapping Strategies in Two Specialties. Issue 2 (14th March 2020) - Kelleher, Matthew; Kinnear, Benjamin; Wong, Sue E. Poynter; O'Toole, Jennifer; Warm, Eric
Abstract: Construct: The construct that is assessed is competency in Pediatrics and Internal Medicine residency training. Background: The Accreditation Council for Graduate Medical Education (ACGME) created milestones to measure learner progression toward competence over time but not as direct assessment tools. Ideal measurement of resident performance includes direct observation and assessment of patient care skills in the workplace. Residency programs have linked these concepts by mapping workplace-based assessments to the milestones of ACGME subcompetencies. Mapping is a subjective process, and little is known about specific techniques or the resulting consequences of mapping program-specific assessment data to larger frameworks of competency. Approach: In this article, the authors compare and contrast the techniques used to link workplace-based assessments called Observable Practice Activities (OPAs) to ACGME subcompetencies in two large academic residency programs from different specialties (Internal Medicine and Pediatrics). Descriptive analysis explored the similarities and differences in the assessment data generated by mapping assessment items to larger frameworks of competency. Results: Each program assessed the core competencies with similar frequencies. The largest discrepancy between the two subspecialties was the assessment of Medical Knowledge, which Internal Medicine assessed twice as often. Pediatrics also assessed the core competency Systems-based Practice almost twice as often as Internal Medicine. Both programs had several subcompetencies that were assessed more or less often than what appeared to be emphasized by the blueprint of mapping. Despite using independent mapping processes, both programs mapped each OPA to approximately three subcompetencies. Conclusions: Mapping workplace-based assessments to the ACGME subcompetencies allowed each program to see the whole of their curricula in ways that were not possible before and to identify existing curricular and assessment gaps. Although each program used similar assessment tools, the assessment data generated were different. The lessons learned in this work could inform other programs attempting to link their own workplace-based assessment elements to ACGME subcompetencies.